Feeding preferences of Melanoplus femurrubrum grasshoppers on native and exotic grasses: behavioral and molecular approaches. Issue 2 (4th October 2015) - Avanesyan, Alina; Culley, Theresa M.
Abstract Generalist insect herbivores, such as grasshoppers, may either avoid feeding on exotic plants, potentially enabling these plants to become invasive in the introduced range, or insects may incorporate exotic plants into their diet, contributing to the biotic resistance of native communities and potentially preventing plant invasions. Accurate determination of insect diet preferences with regard to native and exotic plants can be challenging, but this information is critical for understanding the interaction between native herbivores and exotic plants, and ultimately the mechanisms underlying plant invasions. To address this, we combined behavioral and molecular approaches to accurately compare food consumption of the polyphagous red‐legged grasshopper, Melanoplus femurrubrum (De Geer) (Orthoptera: Acrididae), on native [Andropogon gerardii Vitman and Bouteloua curtipendula (Michx.) Torr.] and exotic, potentially invasive grasses [Miscanthus sinensis Andersson and Bothriochloa ischaemum (L.) Keng] (all Poaceae). We found that M. femurrubrum grasshoppers demonstrated strong feeding preferences toward exotic grasses in experiments with intact plants under both field and greenhouse conditions, but they showed no preference in experiments with clipped leaves. Additionally, we sampled the gut contents of M. femurrubrum collected in the field and identified the ingested plant species based on DNA sequences for the non‐coding region of the chloroplast trnL (UAA) gene. We found that exotic plants were prevalent in the gut contents of grasshoppers collected at study sites in Ohio and Maryland, USA. These results suggest that the generalist herbivore M. femurrubrum does not avoid feeding on exotic grasses with which they do not share coevolutionary history. In addition, by demonstrating greater food consumption of exotic plants, these grasshoppers potentially provide biotic resistance should these grasses escape cultivation and become invasive in the introduced range.